Estimating the Toxicity of Radionuclides in Soil Stored in Drums in the Tuwaitha Area for Determining the Harmful Effects on Humans and Environment - Abd, Saad M.; Al-Mashhadani, Asia H.; Ahmed, Naseer A.; Yas, Rana M. (Iraqi Journal of Science, 2024)
Radioactive waste management is a fundamental issue when using nuclear energy. Therefore, it is necessary to study the health and biological effects on human and environment that these radionuclides cause. The aim of the present study is to estimate the radiotoxicity for radioactive waste in stocked soil in Al-Twaitha city. The radiotoxicity was calculated for each radionuclide, present in the waste, using their dose factor due to ingestion, which is given by the International Commission on Radiological Protection (ICRP) compendium. For the purpose of calculating radiation toxicity, a scenario was built that 20% of the radioactivity during radioactive waste handling processes is in the form of dust that can be inhaled or entered through the mouth or eyes. Drums Characterization System (DCS) provided with portable HPGe hand-held radioisotope identifier was used for the characterization and identification of the radionuclides in the drums and the dose rate was measured by Ludlum radiation detector. The absorbed dose rate ranged from 134.904nGy h-1 to 788400 nGy.h-1, the internal hazard index from 0 to 0.035, representative gamma index from 0 to 0.068, representative alpha index ( from 0 to 0.017, excess lifetime cancer risk (ELCR) value ranged from 0.66× 10-6 to 3.86×10-3 and the range of AEDE from 0.19 mSv to 1103.76 mSv.